Implementation of Protection Consumer in The Sale Agreement Buy Online Marketplace - Gita Maria Rehulina Sembiring; Adri Sadewa Sirait; Roy Nanda Kesuma; Cherin Yorenta Tarigan; Winda Windari Tarigan; Suci Ramadani (International Forum of Researchers and Lecturers, 2026)
The advancement of information technology has rapidly transformed trading patterns in Indonesia, shifting from conventional transactions to online transactions through marketplace platforms. On one hand, this transformation provides convenience and efficiency for both businesses and consumers. On the other hand, it has also given rise to various legal issues, particularly regarding consumer protection. This article aims to examine how legal protection for consumers is implemented in electronic sales agreements on marketplaces, while also identifying the obstacles encountered during its implementation. The study employs a normative juridical approach, using conceptual analysis and legislative review, supplemented by empirical data obtained from interviews. As described, legal protection for consumers in electronic transactions in Indonesia remains suboptimal. Specifically, these challenges include biased law enforcement, low levels of consumer literacy, and ineffective dispute resolution mechanisms. In practice, marketplaces have incorporated consumer protection features such as escrow systems, refund mechanisms, and complaint centers; however, their implementation still suffers from limited transparency and effectiveness. Furthermore, existing regulations are slow to respond to the dynamics of cross-border transactions and ongoing digital innovations. Therefore, comprehensive regulatory reform, stronger enforcement, and enhanced legal and digital literacy among the public are necessary to ensure effective consumer protection.